Gender dependent association of 25-hydroxyvitamin D and circulating leptin in saudi subjects: influence of dyslipidemia - Al-Daghri, Nasser M (Int J Clin Exp Med, 2015)
Background and Objective: Leptin and vitamin D play an important role in obesity development and metabolic effects; however, the association between leptin and vitamin D is not well studied in Saudi subjects. We aimed to examine gender dependent association between serum leptin and 25-OH-VitD in adult Saudi subjects. Subjects and Methods: For this cross-sectional study in a cohort of 259 Saudi adults (100 male, age: 46.4 ± 0.9 yr [mean ± SD]; BMI: 27.8 ± 0.5 Kg/m(2)) and (159 female, age 46.5 ± 0.7 [mean ± SD]; BMI: 28.4 ± 0.4 Kg/m(2)) anthropometrics, fasting bloods, and biochemical data were collected. Serum leptin and 25-hydroxyvitamin D (vitamin D or 25-OH-VitD) were quantified using an enzyme-linked immunosorbent assay. Results: Circulating leptin and vitamin D levels were significantly higher in females compared to male (P<0.001 and P<0.01 respectively). Visceral adiposity index (VAI), triglycerides and total cholesterol were significantly higher (P<0.05, P<0.001, and P<0.05, respectively) while HDL-cholesterol were lower (P<0.001) in male compared to female subjects. In males, vitamin D levels were positively associated with leptin (r = 0.196, P<0.05). Conclusion: Vitamin D was positively associated with serum leptin in male Saudi subjects. Additionally, male subjects were found to be dyslipidemic, which might be a responsible factor for this discordant association between vitamin D and leptin in Saudi population.